KOMUNIKASI DAKWAH ISLAM PADA SINETRON DRAMA RELIGI AMANAH WALI 6 - Silvia Oti Nugraheni; Sofi Aulia Rahmania (LPPM Universitas Bina Bangsa, 2024)
Communication in preaching is considered to have vital value, as one of its functions is to exercise control. This control involves conveying messages and values of virtue as well as prohibitions against doing something bad. Preaching communication includes the roles and functions of communication between all parties, namely the preacher and the audience, from planning, implementation, to evaluation. In this case, the research focuses on the preaching communication of the religious film Amanah Wali 6 in the context of Roland Barthes' semiotics. This research aims to delve deeper into the preaching communication of the characters in the religious film Amanah Wali 6 using Roland Barthes' semiotics, including connotation, denotation, and myth. A methodological approach is used in the form of a descriptive qualitative approach, and a theoretical approach in the form of a semiotic approach. Given the type of research object in the form of a film, the listening method is used with the free listening technique (SLBC) and the note-taking technique (phonemic transcription). The results obtained are that the film Amanah Wali 6 is full of advice towards goodness and virtue, which is the goal of preaching